Edukasi Ragam Investasi Digital untuk Meningkatkan Peluang Passive Income UMKM Kota Malang - Dhika Maha Putri; Dwi Narullia; Putri Regina Prayoga; Yongky Teguh Setiaji (Universitas Muhammadiyah Malang, 2024)
Purpose – This activity aims to provide understanding to Micro, Small and Medium Enterprises (MSMEs) in managing their income and capital flows Design/methodology/approach – This service method is carried out by involving a combination of socialization and education programs that emphasize the importance of investing, providing practical guidance, and supervising digital investments made by MSME participants. Findings – After the service activities are carried out, it can increase knowledge and interest in digital investment among MSME players in the city of Malang so that MSME enthusiasm for investment as a passive income stream increases, while protecting them from fraud in investment Originality/value – Activities focus on the goal of broadening the perspective of MSME players regarding digital investment